2016
DOI: 10.4081/itjm.2016.758
|View full text |Cite
|
Sign up to set email alerts
|

The impact of saffron (Crocus sativus) supplementation on visual function in patients with dry age-related macular degeneration

Abstract: The aim was to evaluate the impact of saffron supplementation on visual function in patients with dry age-related macular degeneration (ARMD). Fifty-four participants, 23 male and 31 female, with dry ARMD were assigned to one of the following two groups. The treatment group (n=29) consumed 50 mg saffron daily during a 3- month period, while 25 subjects served as the control group. Visual acuity, contrast sensitivity, and retinal thickness were measured at the beginning and at the end of the study. Quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Furthermore, crocetin can cause protective effects by triggering MAPK-dependent survival pathways. In line with our observation, that the protective role of crocetin is particularly effective when given as a pre-treatment, i.e., before the addition of the damaging substance (TBHP), first trials using short-term saffron supplementation reported improved retinal flicker sensitivity, contrast sensitivity, and decrease in central macular thickness, in patients suffering from early AMD [42,45,46]. The protection caused by pre-treatment with crocetin is in a similar range as established antioxidants, such as vitamins C and E. Interestingly, vitamins C and E were shown to be useful for suppression of macular degeneration progression in AMD patients [93] or retinal oxidative stress models [94,95] and have been used in other studies to compare the efficiency of specific flavonoids in protection of RPE cells from oxidative stress [28].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, crocetin can cause protective effects by triggering MAPK-dependent survival pathways. In line with our observation, that the protective role of crocetin is particularly effective when given as a pre-treatment, i.e., before the addition of the damaging substance (TBHP), first trials using short-term saffron supplementation reported improved retinal flicker sensitivity, contrast sensitivity, and decrease in central macular thickness, in patients suffering from early AMD [42,45,46]. The protection caused by pre-treatment with crocetin is in a similar range as established antioxidants, such as vitamins C and E. Interestingly, vitamins C and E were shown to be useful for suppression of macular degeneration progression in AMD patients [93] or retinal oxidative stress models [94,95] and have been used in other studies to compare the efficiency of specific flavonoids in protection of RPE cells from oxidative stress [28].…”
Section: Discussionsupporting
confidence: 83%
“…In this study, the protective effect of crocetin against TBHP-induced oxidative stress is consistent with the impact of saffron in six clinical trials related to AMD. In these clinical trials, positive effects of saffron on patients vision were reported by significant improvements in objective (ERG) and subjective measures (Snellen, LogMar, EDTRS charts) of visual acuity [42][43][44][45][46][47] and increase in contrast sensitivity (CS) [46]. However, the mechanism and pathways involved in the beneficial effects of saffron on retinal tissues have not been fully identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the performed literature searches, there were eight published clinical studies that have assessed the impact of oral supplementation with saffron or one of its constituents on vision-related parameters in adults with ocular diseases [32,33,34,35,36,37,38,39]. Of these, six were randomized controlled trials (RCTs) [32,35,36,37,38,39], while two are longitudinal interventional clinical studies reporting on pre- (baseline) versus post-intervention comparisons without a comparator/control group [33,34]. For the two latter studies that are from the same group and report on different outcome measures, it is also not clear whether their design involves, at least partly, participants of the same cohort, and efforts to contact the corresponding authors in order to clarify this point were not successful [33,34].…”
Section: Clinical Evidence Regarding the Impact Of Oral Supplementmentioning
confidence: 99%
“…Age related macular degeneration : six published clinical studies assessed vision-related parameters in AMD patients under oral saffron supplementation (Table 2) [32,33,34,35,36,37]. Based on these, both objective (ERG) and subjective measures (Snellen, LogMar, EDTRS charts) of visual acuity were shown to significantly improve with all tested dosages of saffron (daily dose range: 20–50 mg), even after short-term oral supplementation (e.g., three months) [32,33,34,35,36,37]. Central macular thickness (CMT) [35] and contrast sensitivity (CS) [36] were also assessed in certain studies (Table 2), with the latter reportedly increasing with saffron supplementation [36], whilst the former was shown to decrease only in wet, but not dry AMD following saffron supplementation [35].…”
Section: Clinical Evidence Regarding the Impact Of Oral Supplementmentioning
confidence: 99%